The effect of procedural time on dysplasia detection rate during endoscopic surveillance of Barrett’s esophagus - Vithayathil, Mathew; Modolell, Ines; Ortiz-Fernandez-Sordo, Jacobo; Pappas, Apostolos; Januszewicz, Wladyslaw; O’Donovan, Maria; Bianchi, Michele; White, Jonathan R.; Kaye, Philip; Ragunath, Krish; di Pietro, Massimiliano (Endoscopy, 2023)
Background Endoscopic surveillance of Barrett’s esophagus (BE) with Seattle protocol biopsies is time-consuming and inadequately performed in routine practice. There is no recommended procedural time for BE surveillance. We investigated the duration of surveillance procedures with adequate tissue sampling and effect on dysplasia detection rate (DDR).Methods We performed post hoc analysis from the standard arm of a crossover randomized controlled trial recruiting patients with BE (≥C2 and/or ≥M3) and no clearly visible dysplastic lesions. After inspection with white-light imaging, targeted biopsies of subtle lesions and Seattle protocol biopsies were performed. Procedure duration and biopsy number were stratified by BE length. The effect of endoscopy-related variables on DDR was assessed by multivariable logistic regression.Results Of 142 patients recruited, 15 (10.6 %) had high grade dysplasia/intramucosal cancer and 15 (10.6 %) had low grade dysplasia. The median procedural time was 16.5 minutes (interquartile range 14.0–19.0). Endoscopy duration increased by 0.9 minutes for each additional 1 cm of BE length. Seattle protocol biopsies had higher sensitivity for dysplasia than targeted biopsies (86.7 % vs. 60.0 %; P = 0.045). Longer procedural time was associated with increased likelihood of dysplasia detection on quadrantic biopsies (odds ratio [OR] 1.10, 95 %CI 1.00–1.20, P = 0.04), and for patients with BE > 6 cm also on targeted biopsies (OR 1.21, 95 %CI 1.04–1.40; P = 0.01).Conclusions In BE patients with no clearly visible dysplastic lesions, longer procedural time was associated with increased likelihood of dysplasia detection. Adequate time slots are required to perform good-quality surveillance and maximize dysplasia detection.